Gestión Administrativa - Financiera y sus efectos en la calidad del servicio de la Dirección Distrital de Educación 12D01 Babahoyo, Baba, Montalvo - Bajaña Piza, Edinson Eber (2017)
The present research project focuses on the effect of administrative and financial management with the quality of services of the District Directorate of Education 12D01 Babahoyo, Baba and Montalvo. Research was done on the international, national and local influence of administrative and financial management, showing the way in which it can influence the quality of service. A literature review was carried out that was relevant to the research points that were: administrative - financial management and quality of service. Each one of the subjects was shown in a detailed way, but limiting information and only with the direct relation with the subject of study so that there was a clear understanding of the points that are treated. Interview with the District Director of Education to the Directors of Schools. Another method of gathering information was the surveys, which were directed to administrative personnel, academics, students and parents of families. In order to know what your opinion is regarding administrative and financial management and the quality of service offered by the school and the District Directorate of Education. Thanks to the analysis of the results, it is possible to determine what is going to be done? How are you going to do? What is it going to do? After presenting the proposal and the results of the suggested alternatives.